(untitled) (Academicia Globe: Inderscience Research, 2023)
This article shows the ways of implementing society, human experiences, personality, human dignity through pictures, in the works of Nazar Eshankul. In his works, the humiliation and difficulties of individuals are reflected not through words, but through paints.